2023
DOI: 10.1186/s13020-023-00836-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality evaluation methods of chinese medicine based on scientific supervision: recent research progress and prospects

Zhangmei Chen,
Chi Teng Vong,
Tiejun Zhang
et al.

Abstract: Traditional Chinese medicine (TCM) is increasingly getting attention worldwide, as it has played a very satisfactory role in treating COVID-19 during these past 3 years, and the Chinese government highly supports the development of TCM. The therapeutical theory and efficacies of Chinese medicine (CM) involve the safety, effectiveness and quality evaluation of CM, which requires a standard sound system. Constructing a scientific and reasonable CM quality and safety evaluation system, and establishing high-quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…Chinese medicine has a long history of treating various diseases with few toxic side effects [21]. Chinese herbal formulas usually consist of a variety of herbs with synergistic effects for the treatment of various diseases [22] [23]. Studies have confirmed that Chinese herbs have robust pharmacological effects and have received more and more attention in the treatment of CKD [24][25] [26].…”
Section: Introductionmentioning
confidence: 99%
“…Chinese medicine has a long history of treating various diseases with few toxic side effects [21]. Chinese herbal formulas usually consist of a variety of herbs with synergistic effects for the treatment of various diseases [22] [23]. Studies have confirmed that Chinese herbs have robust pharmacological effects and have received more and more attention in the treatment of CKD [24][25] [26].…”
Section: Introductionmentioning
confidence: 99%